Malignant peripheral nerve sheath tumor of retroperitoneum involving small and large bowel: A rare case report - Sharma, Jagannath D; Kalita, Upasana; Deka, Muktanjalee; Bharadwaj, Barasha; Beso, Adahra Patricia (Indian Journal of Case Reports, 2024)
Malignant peripheral nerve sheath tumors (MPNSTs) are rare and aggressive, soft-tissue sarcomas having a high rate of recurrence which largely occur in the extremities and the head-and-neck region. Gastrointestinal (GI) MPNSTs are rare. To date, only a few cases have been reported. We report the case of a 50-year-old man who presented with pain and a lump in his abdomen for 1 year. Clinically, the case was thought to be retroperitoneal neurofibroma. A computed tomography scan revealed an intra-abdominal large well-defined lobulated mass predominantly on the left side. Exploratory laparotomy and resection of the tumor were done as large and small bowel mesentery masses. Histopathological examination showed a spindle cell neoplasm composed of interlacing fascicles of slender to plump spindle cells with wavy buckled nuclei. Cells showed moderate to marked anisonucleosis with hyperchromatic and vesicular nuclei with prominent nucleoli along with many pleomorphic cells with multiple nuclei and many mitosis. The tumor seemed to be infiltrating the wall of the small bowel and colon. On immunohistochemistry, tumor cells were positive for vimentin, focally positive for S100, and negative for smooth muscle actin. Thus, the diagnosis of MPNST was confirmed. This case highlights that, although rare, the possibility of MPNST of retroperitoneum should be considered as a differential diagnosis in an unexplored retroperitoneal mass.